Changes in radiocesium concentrations in epigeic earthworms in relation to the organic layer 2.5 years after the 2011 Fukushima Dai-ichi Nuclear Power Plant accident. (July 2015) - Hasegawa, Motohiro; Kaneko, Shinji; Ikeda, Shigeto; Akama, Akio; Komatsu, Masabumi; Ito, Masamichi T.
Abstract: We reported previously that radiocesium ( 137 Cs) concentrations in earthworms increased with those in litter and/or soil in Fukushima Prefecture forests 0.5 y after the Fukushima Dai-ichi Nuclear Power Plant (FDNPP) accident. This study provides further results for 1.5 and 2.5 y after the accident and discusses temporal changes in 137 Cs concentrations and transfer factors (TF) from litter to earthworms to better understand the mechanisms by which 137 Cs enters soil food webs. The concentration of 137 Cs in accumulated litter on the forest floor rapidly decreased, and the concentration in soil (0–5-cm depth) increased over time from 0.5 to 1.5 y, but changed only moderately from 1.5 to 2.5 y. The concentration of 137 Cs in earthworms consistently decreased during the study period; values 2.5 y after the accident were 18.8–68.5% of those 0.5 y after the accident. The TFs from accumulated litter to earthworms decreased over time: 0.24 ± 0.08 (mean ± SD) at 0.5 y and 0.16 ± 0.04 at 2.5 y. This decrease may be a result of decreases in the bioavailability of 137 Cs in litter and the surface soil layer. Changes in 137 Cs bioavailability should be continuously tracked to determine any changes in the relationship between radiocesium concentrations in earthworms and that in accumulated litter or soil. Highlights: We investigated radiocesium concentrations in soil, litter and earthworms. Radiocesium concentration in earthworms consistently decreased after the accident. Transfer factors from accumulated litter to earthworms tended to be smaller after 2.5 years. The 134 Cs/ 137 Cs ratio in earthworms was similar to that in accumulated litter.